Imperfect Debugging Software Reliability Growth Model for the Rayleigh failure time distribution (International Journal of Engineering and Computer Science, 2016)
Non homogeneous Poisson process software reliability models assume perfect debugging. However in the testing process there is a chance of introducing new faults when detected faults are removed. A model with this concept is called imperfect debugging software reliability model. Imperfect debugging software reliability models proposed in the literature assume a constant or monotonically decreasing fault introduction function. In this article we propose a software reliability model that considers Rayleigh distribution fault content function. The model can capture increasing/decreasing nature of fault introduction rate per fault. The parameters of the model are estimated using maximum likelihood method.  A real data are used to verify the model.